No evidence for differential sociosexual behavior and space use in the color morphs of the European common wall lizard (Podarcis muralis). Issue 20 (8th October 2020) - Abalos, Javier; Pérez i de Lanuza, Guillem; Bartolomé, Alicia; Liehrmann, Océane; Laakkonen, Hanna; Aubret, Fabien; Uller, Tobias; Carazo, Pau; Font, Enrique
Abstract: Explaining the evolutionary origin and maintenance of color polymorphisms is a major challenge in evolutionary biology. Such polymorphisms are commonly thought to reflect the existence of alternative behavioral or life‐history strategies under negative frequency‐dependent selection. The European common wall lizard Podarcis muralis exhibits a striking ventral color polymorphism that has been intensely studied and is often assumed to reflect alternative reproductive strategies, similar to the iconic "rock–paper–scissors" system described in the North American lizard Uta stansburiana . However, available studies so far have ignored central aspects in the behavioral ecology of this species that are crucial to assess the existence of alternative reproductive strategies. Here, we try to fill this gap by studying the social behavior, space use, and reproductive performance of lizards showing different color morphs, both in a free‐ranging population from the eastern Pyrenees and in ten experimental mesocosm enclosures. In the natural population, we found no differences between morphs in site fidelity, space use, or male–female spatial overlap. Likewise, color morph was irrelevant to sociosexual behavior, space use, and reproductive success within experimental enclosures. Our results contradict the commonly held hypothesis that P. muralis morphs reflect alternative behavioral strategies, and suggest that we should instead turn our attention to alternative functional explanations. Abstract : Ventral color morphs in wall lizards have often been assumed to reflect alternative reproductive strategies. In this study, we study the social behavior, space use, and reproductive success of Podarcis muralis color morphs both in a free‐ranging population from the eastern Pyrenees and in ten experimental mesocosm enclosures. Overall, our results suggest that color morphs do not reflect alternative strategies concerning sociosexual behavior or space use.